An olfactory receptor from Apolygus lucorum (Meyer-Dur) mainly tuned to volatiles from flowering host plants. (August 2015) - Yan, Shu-Wei; Zhang, Jin; Liu, Yang; Li, Guo-Qing; Wang, Gui-Rong
Graphical abstract: Highlights: We identify 4 olfactory receptors from Apolygus lucorum . OR28 is sensitively tuned to ( Z )-3-Hexenyl acetate and few structurally similar compounds. OR28 responds to three attractive flowering compounds Butyl acrylate, Butyl propionate and Butyl butyrate. Abstract: Apolygus lucorum (Meyer-Dür) (Hemiptera: Miridae) is one of the most serious agricultural pests, feeding on a wide range of cultivated plants, including cotton, cereals and vegetables in the north of China. This insect can frequently switch between habitats and host plants over seasons and prefer plants in bloom. A. lucorum relies heavily on olfaction to locate its host plants finely discriminating different plant volatiles in the environment. Despite its economical importance, research on the olfactory system of this species has been so far very limited. In this study, we have identified and characterized an olfactory receptor which is sensitively tuned to ( Z )-3-Hexenyl acetate and several flowering compounds. Besides being present in the bouquet of some flowers, these compounds are produced by plants that have suffered attacks and are supposed to act as chemical messengers between plants. This OR may play an important role in the selection of host plants.